Novel silicon-based potassium ion solid electrolyte material as well as optimized and modified preparation method and application thereof

By developing a new silicon-based potassium ion solid electrolyte material K(3-x)LnPxSi(3-x)O9, the limitations of existing materials in ion transport and electrochemical stability are solved, high ionic conductivity and stability are achieved, and its application performance in large-scale energy storage systems is improved.

CN119833734AActive Publication Date: 2025-04-15HUNAN UNIV
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510030038.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing potassium ion solid electrolyte materials have limitations in ion transport and electrochemical stability, resulting in limited application in large-scale energy storage systems.

Method used

A new silicon-based potassium ionic solid electrolyte material is developed, with the chemical formula K(3-x)LnPxSi(3-x)O9, x=0~0.3, Ln is Y or Gd, with a three-dimensional network structure and high ionic conductivity. The material is prepared by specific precursor mixing and high temperature sintering processes, optimizing the crystal structure and potassium ion transport path.

Benefits of technology

Potassium ion solid electrolyte materials with high ionic conductivity and physical/electrochemical stability have improved their performance and application prospects in potassium ionic solid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833734A_ABST
    Figure CN119833734A_ABST
Patent Text Reader

Abstract

The invention discloses a novel silicon-based potassium ion solid electrolyte material and an optimized and modified preparation method and application thereof, and belongs to the technical field of potassium ion solid electrolyte materials. The chemical general formula of the material is K3-xLnSi (3-x) PxO9 (x = 0-0.3), wherein Ln is Y or Gd. The solid electrolyte material is prepared by a solid phase method, has the advantages of simple preparation method and strong ionic conductivity, has better practical value, and can be applied to potassium ion solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of potassium ion batteries, and in particular to a silicon-based potassium ion solid electrolyte material and its optimized modification, and in particular to a novel silicon-based potassium ion solid electrolyte material and its optimized modified preparation method and application. Background Art

[0002] Large-scale energy storage systems can store unevenly distributed and intermittent wind and solar energy and output stable, flexible and controllable energy, which is conducive to solving energy problems and promoting sustainable economic development. In the field of large-scale energy storage systems, traditional liquid lithium-ion batteries have shown certain limitations, among which the price is relatively high and the safety is difficult to be fully guaranteed. This is mainly reflected in the fact that the earth's lithium resources are scarce and the distribution is severely uneven, making the cost difficult to control and predict. Secondly, liquid batteries require the use of a large amount of organic solvents, which leads to safety hazards such as flammability, volatility and leakage. In the face of these problems, it is completely necessary and must be practiced to find a highly potential and effective alternative to lithium-ion batteries.

[0003] It is worth noting that the potassium content in the earth's crust is high and there is no geographical restriction. As people's research on potassium-ion batteries deepens, potassium-ion batteries have attracted much attention due to their low cost, eco-friendliness, and high energy density. The safety hazards of organic solvents in liquid lithium-ion batteries are also replicated in liquid potassium-ion battery systems. And large-scale energy storage systems will further amplify this problem, so it is particularly important to develop potassium-ion solid-state batteries with higher safety and higher energy density. They are highly competitive in terms of low cost, high safety and energy density, and at the same time show great application value and commercial prospects.

[0004] Potassium ion solid electrolyte is the most important component of potassium solid-state batteries. The development of high-performance and high-quality potassium ion solid electrolyte is a common pursuit of related workers. At present, some research work has achieved great success, but due to the large ionic radius and high mass of potassium ions themselves, there are certain difficulties in the transmission of potassium ions in the electrolyte. The types and quantities of reported potassium ion solid electrolytes are very limited, and the ionic conductivity is generally low. At the same time, only a few solid-state metal potassium batteries have successfully carried out electrochemical performance tests. The research on potassium ion solid electrolyte conductors is still in its early stages. Exploring potential potassium ion conductors with high ionic conductivity and physical / electrochemical stability is a necessary and challenging task. Summary of the invention

[0005] In view of the limitations of existing solid electrolyte types, the present invention provides a new silicon-based potassium ion solid electrolyte material and its optimized and modified preparation method and application. The purpose is to develop and prepare a new solid electrolyte material suitable for potassium ion conductivity; expand the applicable system of potassium ion solid electrolyte materials; and provide a universal research idea for optimizing and modifying the transmission of ions (such as potassium ions).

[0006] The present invention provides a novel silicon-based potassium ion solid electrolyte material, characterized in that the novel silicon-based potassium ion solid electrolyte material has a chemical formula of K (3-x) LnP x Si (3-x) O 9 , x = 0 ~ 0.3, Ln is Y or Gd, each pair of silicon-oxygen tetrahedrons in the crystal framework share a vertex, forming a [Si 3 O 9 ] spiral chain is a silicate skeleton with a composite group, and the anion [LnSi 3 O 9 ] n 3n- The skeleton is a three-dimensional channel system, the main channels are parallel to the

[100] and

[010] directions, three crystallographically different K atom positions are distributed inside the skeleton, and the solid electrolyte material is a three-dimensional network structure.

[0007] The present invention also provides a method for preparing the novel silicon-based potassium ion solid electrolyte material, which is characterized by comprising the following steps:

[0008] Potassium salt, trivalent metal oxide, silicon dioxide and phosphate are taken as precursors, and a solvent is added at a ratio of 1 g / mL according to the mass of the precursor, and then the precursor mixture is fully ball-milled to obtain a uniform precursor mixture; the solvent is dried to remove the precursor mixture, and the mixture is placed in a muffle furnace for calcination at 500-900° C. to promote the decomposition of the precursor and the synthesis of the intermediate phase; the intermediate phase is pressurized by a unidirectional cold press at 200-400 MPa for 10-60 seconds to obtain a complete disc; the disc is calcined at 1100-1300° C. in a muffle furnace to obtain a solid electrolyte material K (3-x) LnP x Si (3-x) O 9 .

[0009] Preferably, according to one or more embodiments of the present invention, the potassium salt in the method for preparing the novel silicon-based potassium ion solid electrolyte material is any one of potassium carbonate, potassium acetate and potassium nitrate.

[0010] Preferably, according to one or more embodiments of the present invention, the trivalent metal oxide in the method for preparing the novel silicon-based potassium ion solid electrolyte material is any one of yttrium oxide or gadolinium oxide.

[0011] Preferably, according to one or more embodiments of the present invention, the phosphate in the method for preparing the novel silicon-based potassium ion solid electrolyte material is any one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, potassium hypophosphite, and tripotassium phosphate.

[0012] Preferably, according to one or more embodiments of the present invention, in the method for preparing the novel silicon-based potassium ion solid electrolyte material, the solvent is any one of isopropanol and acetone, the drying temperature is 60-120° C., and the drying time is 6-36 h.

[0013] Preferably, according to one or more embodiments of the present invention, the calcination time at 500-900° C. in the preparation method of the novel silicon-based potassium ion solid electrolyte material is 3-12 h.

[0014] Preferably, according to one or more embodiments of the present invention, the calcination time at 1100-1300° C. in the preparation method of the novel silicon-based potassium ion solid electrolyte material is 1-24 h.

[0015] Preferably, according to one or more embodiments of the present invention, the content of the heterovalent element P in the preparation method of the novel silicon-based potassium ion solid electrolyte material needs to be explored within the range of maintaining performance improvement, and its content is between 0 and 0.3.

[0016] The present invention also provides application of the novel silicon-based potassium ion solid electrolyte material as a solid electrolyte.

[0017] The technical solution of the present invention has the following advantages:

[0018] The present invention provides a material system suitable for potassium ion solid electrolyte. The material system is a three-dimensional network structure, and there is a large ion migration bottleneck in its crystal structure. The distance between potassium ions is relatively close, which provides favorable conditions for the rapid migration of ions. The potassium ion solid electrolyte of this system is tested for AC impedance and ionic conductivity. 3 YS 3 O 9 At 60℃, the ionic conductivity is 7.92×10 -3 mS / cm,K 3 G JZ 3 O 9 At 60℃, the ionic conductivity is 1.02×10 -2 mS / cm. The heterovalent element P is further introduced into the system for optimization and modification, the purpose of which is to adjust the crystal structure of the material on the one hand, and to create potassium ion vacancies or add new potassium ion sites on the other hand, thereby improving the performance. 2.8 GDP 0.2 Si 2.8 O9 At 60℃, the ionic conductivity is 8.82×10 -2 mS / cm, with high ionic conductivity. (3-x) LnP x Si (3-x) O 9 The present invention also shows that it has good application prospects as a potassium ion solid electrolyte material in potassium ion solid-state batteries, and provides a new idea for the development and optimization of potassium ion solid electrolyte materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 The potassium ion solid electrolyte K obtained in Examples 1-3 of the present invention 3 YS 3 O 9 XRD pattern of

[0021] Figure 2 The potassium ion solid electrolyte K obtained in Examples 1-3 of the present invention 3 YS 3 O 9 Ionic conductivity diagram of

[0022] Figure 3 The potassium ion solid electrolyte K obtained in Example 3 of the present invention 3 YS 3 O 9 SEM images of

[0023] Figure 4 The potassium ion solid electrolyte K obtained in Example 3 of the present invention 3 YS 3 O 9 The crystal structure diagram of

[0024] Figure 5 The potassium ion solid electrolyte K obtained in Examples 4-6 of the present invention 3 G JZ 3 O 9 XRD pattern of

[0025] Figure 6 The potassium ion solid electrolyte K obtained in Examples 4-6 of the present invention3 G JZ 3 O 9 Ionic conductivity diagram of

[0026] Figure 7 The potassium ion solid electrolyte K obtained in Example 6 of the present invention 3 G JZ 3 O 9 SEM images of

[0027] Figure 8 The potassium ion solid electrolyte K obtained in Example 6 of the present invention 3 G JZ 3 O 9 The crystal structure diagram of

[0028] Fig. 9 The potassium ion solid electrolyte K obtained in Examples 6-9 of the present invention (3-x) GDP x Si (3-x) O 9 (x=0~0.3) XRD pattern;

[0029] Fig.10 The potassium ion solid electrolyte K obtained in Examples 6-9 of the present invention (3-x) GDP x Si (3-x) O 9 Ionic conductivity diagram of (x = 0 to 0.3);

[0030] Fig.11 The potassium ion solid electrolyte K obtained in Example 8 of the present invention 2.8 GDP 0.2 Si 2.8 O 9 SEM images of

[0031] Fig.12 The potassium ion solid electrolyte K obtained in Example 8 of the present invention 2.8 GDP 0.2 Si 2.8 O 9 Voltage window test CV diagram.

[0032] Fig.13 The potassium ion solid electrolyte K obtained in Example 8 of the present invention 2.8 GDP 0.2 Si 2.8 O 9 Cycling performance diagram of matching Prussian blue positive electrode and potassium-carbon composite negative electrode.

[0033] Fig.14 The potassium ion solid electrolyte K obtained in Example 8 of the present invention 2.8GDP 0.2 Si 2.8 O 9 Cycling performance diagram of matching high voltage potassium vanadium fluorophosphate positive electrode and potassium carbon composite negative electrode. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. In addition, it should be understood that after reading the contents disclosed in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention.

[0035] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, instruments, etc. used in the following examples are all commercially available unless otherwise specified.

[0036] Example 1

[0037] A potassium ion solid electrolyte material K 3 YS 3 O 9 , and its preparation method is:

[0038] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is yttrium oxide, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: yttrium element: silicon element = 3:1:3. The precursor solvent is isopropanol. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at 250rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to a 120°C forced air drying oven and dried for 12 hours to remove the solvent isopropanol.

[0039] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A1.

[0040] Experimental method of sintering: Sample A1 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A1 was weighed and placed in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B1. Sample B1 was then calcined in an alumina crucible at a sintering temperature of 1200°C for 5 hours to obtain sample C1.

[0041] Example 2

[0042] A potassium ion solid electrolyte material K 3 YS 3 O9 , and its preparation method is:

[0043] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is yttrium oxide, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: yttrium element: silicon element = 3:1:3. The precursor solvent is isopropanol. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at 250rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to a 120°C forced air drying oven and dried for 12 hours to remove the solvent isopropanol.

[0044] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A2.

[0045] Experimental method of sintering: The sample A2 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A2 was weighed and kept in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B2. Then, the sample B2 was calcined in an alumina crucible, where the sintering temperature was 1250°C and the heat preservation time was 5 hours to obtain the sample C2.

[0046] Example 3

[0047] A potassium ion solid electrolyte material K 3 YS 3 O 9 , and its preparation method is:

[0048] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is yttrium oxide, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: yttrium element: silicon element = 3:1:3. The precursor solvent is isopropanol. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at 250rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to a 120°C forced air drying oven and dried for 12 hours to remove the solvent isopropanol.

[0049] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A3.

[0050] Experimental method of sintering: Sample A3 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A3 was weighed and placed in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B3. Sample B3 was then calcined in an alumina crucible at a sintering temperature of 1300°C for 5 hours to obtain sample C3.

[0051] The potassium ion solid electrolytes obtained in the above Examples 1-3 were subjected to XRD characterization: the samples C1-C3 were ground into powder in a mortar, wherein the test 2θ angle of XRD characterization was 10-80°.

[0052] Figure 1 This is the XRD pattern obtained from the test of samples C1-C3.

[0053] The potassium ion solid electrolyte obtained in the above example was subjected to an AC impedance test to calculate the ionic conductivity: silver paste was applied to both sides of the samples C1-C3, and dried in a blast drying oven at 70°C to obtain a sandwich-shaped (Ag / K 3 YS 3 O 9 / Ag) symmetrical battery. The ionic conductivity was calculated by AC impedance characterization, where the test frequency range was 10 6 -0.1Hz, the impedance of the electrolyte sheet is obtained by fitting and substituted into the formula σ=L / (RS), where σ is the ionic conductivity, L is the thickness of the electrolyte sheet, R is the impedance obtained by impedance fitting, and S is the area directly opposite to the electrolyte sheet.

[0054] Figure 2 It is electrolyte K 3 YS 3 O 9 Comparison of ionic conductivity at different calcination temperatures shows that the sample calcined at 1300 degrees is the best, and at 60 degrees is 7.92×10 -3 mS / cm, indicating that this solid electrolyte has excellent ionic conductivity.

[0055] Figure 3 It is calcined at 1300 degrees K 3 YS 3 O 9 Scanning electron microscope image of .

[0056] Figure 4 It's K 3 YS 3 O 9 Crystal structure diagram.

[0057] Example 4

[0058] A potassium ion solid electrolyte material K 3 G JZ3 O 9 , and its preparation method is:

[0059] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is gadolinium oxide, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: gadolinium element: silicon element = 3:1:3. The precursor solvent is acetone. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at 250 rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to an 80°C forced air drying oven and dried for 3 hours to remove the solvent acetone.

[0060] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A4.

[0061] Experimental method of sintering: The sample A4 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A4 was weighed and placed in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B4. Then, the sample B4 was buried in an alumina crucible with a mother powder sintering temperature of 1200°C and a heat preservation time of 12 hours to obtain a sample C4.

[0062] Example 5

[0063] A potassium ion solid electrolyte material K 3 G JZ 3 O 9 , and its preparation method is:

[0064] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is gadolinium oxide, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: gadolinium element: silicon element = 3:1:3. The precursor solvent is acetone. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at 250 rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to an 80°C forced air drying oven and dried for 3 hours to remove the solvent acetone.

[0065] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A5.

[0066] Experimental method of sintering: Sample A5 obtained by the above pretreatment was fully ground again in a mortar, and then a proper amount of sample A5 was weighed and kept in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B5. Then, sample B5 was calcined in an alumina crucible with a mother powder, wherein the sintering temperature was 1250°C and the heat preservation time was 12 hours, and sample C5 was obtained.

[0067] Example 6

[0068] A potassium ion solid electrolyte material K 3 G JZ 3 O 9 , and its preparation method is:

[0069] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is gadolinium oxide, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: gadolinium element: silicon element = 3:1:3. The precursor solvent is acetone. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at 250 rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to an 80°C forced air drying oven and dried for 3 hours to remove the solvent acetone.

[0070] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A6.

[0071] Experimental method of sintering: The sample A6 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A6 was weighed and placed in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B6. Then, the sample B6 was buried in an alumina crucible with a mother powder sintering temperature of 1300°C and a heat preservation time of 12 hours to obtain a sample C6.

[0072] The potassium ion solid electrolytes obtained in Examples 4-6 were subjected to XRD characterization: Samples C4-C6 were ground into powder in a mortar, wherein the test 2θ angle of XRD characterization was 10-80°.

[0073] Figure 5 This is the XRD pattern obtained from the test of samples C4-C6.

[0074] Figure 6 It is electrolyte K 3 G JZ 3 O 9 Comparison of ionic conductivity at different calcination temperatures shows that the sample calcined at 1300 degrees is the best, and at 60 degrees is 1.02×10 -2mS / cm, indicating that this solid electrolyte has excellent ionic conductivity.

[0075] Figure 7 It is calcined at 1300 degrees K 3 G JZ 3 O 9 Scanning electron microscope image of .

[0076] Figure 8 It's K 3 G JZ 3 O 9 Crystal structure diagram.

[0077] Example 7

[0078] A potassium ion solid electrolyte material K 2.9 GDP 0.1 Si 2.9 O 9 , and its preparation method is:

[0079] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is gadolinium oxide, phosphate is ammonium dihydrogen phosphate, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: gadolinium element: phosphorus element: silicon element = 2.9:1:0.1:2.9. The precursor solvent is acetone. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at a speed of 250 rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to a blast drying oven at 80°C and dried for 3 hours to remove the solvent acetone.

[0080] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A7.

[0081] Experimental method of sintering: The sample A7 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A7 was weighed and placed in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B7. Then, the sample B7 was buried in an alumina crucible with a mother powder sintering temperature of 1300°C and a heat preservation time of 12 hours to obtain a sample C7.

[0082] Example 8

[0083] A potassium ion solid electrolyte material K 2.8 GDP 0.2 Si 2.8 O 9 , and its preparation method is:

[0084] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is gadolinium oxide, phosphate is ammonium dihydrogen phosphate, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: gadolinium element: phosphorus element: silicon element = 2.8:1:0.2:2.8. The precursor solvent is acetone. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at a speed of 250 rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to a blast drying oven at 80°C and dried for 3 hours to remove the solvent acetone.

[0085] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A8.

[0086] Experimental method of sintering: The sample A8 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A8 was weighed and placed in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B8. Then, the sample B8 was buried in an alumina crucible with a mother powder sintering temperature of 1300°C and a heat preservation time of 12 hours to obtain a sample C8.

[0087] Example 9

[0088] A potassium ion solid electrolyte material K 2.7 GDP 0.3 Si 2.7 O 9 , and its preparation method is:

[0089] Experimental method of precursor mixture: potassium salt is anhydrous potassium carbonate, rare earth metal oxide is gadolinium oxide, phosphate is ammonium dihydrogen phosphate, and silicon dioxide, wherein the mass of each component is weighed according to the molar mass ratio of potassium element: gadolinium element: phosphorus element: silicon element = 2.7:1:0.3:2.7. The precursor solvent is acetone. The prepared precursor material and solvent are sealed in a ball mill jar and ball milled at a speed of 250 rpm in a planetary ball mill for 6 hours. The mixed slurry is then transferred to a blast drying oven at 80°C and dried for 3 hours to remove the solvent acetone.

[0090] Experimental method for pretreatment: The precursor mixture obtained above was first fully ground in a mortar, and then the powder was transferred to an alumina crucible and pretreated in a muffle furnace, wherein the calcination temperature was 600°C and the insulation time was 5 hours to obtain sample A9.

[0091] Experimental method of sintering: The sample A9 obtained by the above pretreatment was fully ground again in a mortar, and then an appropriate amount of sample A9 was weighed and kept in a tablet pressing mold at a unidirectional pressure of 400 MPa for 60 seconds to obtain a dense sample B9. Then, the sample B9 was buried in an alumina crucible for mother powder sintering, wherein the sintering temperature was 1300°C and the heat preservation time was 12 hours to obtain the sample C9.

[0092] The potassium ion solid electrolytes obtained in the above Examples 7-9 were subjected to XRD characterization: the samples C7-C9 were ground into powder in a mortar, wherein the test 2θ angle of XRD characterization was 10-80°.

[0093] Fig. 9 This is the XRD pattern obtained from the test of samples C6-C9.

[0094] Fig.10 It is electrolyte K (3-x) GDP x Si (3-x) O 9 (x = 0 ~ 0.3) ionic conductivity comparison, where K 2.8 GDP 0.2 Si 2.8 O 9 The sample is optimal, which is 8.82×10 -2 mS / cm, indicating that this solid electrolyte has high ionic conductivity.

[0095] Fig.11 It's K 2.8 GDP 0.2 Si 2.8 O 9 Scanning electron microscope image of .

[0096] Fig.12 It's K 2.8 GDP 0.2 Si 2.8 O 9 Voltage window test CV diagram.

[0097] Fig.13 Is the application K 2.8 GDP 0.2 Si 2.8 O 9 Cycling performance diagram of solid electrolyte matched Prussian blue positive electrode and potassium-carbon composite negative electrode.

[0098] Fig.14 Is the application K 2.8 GDP 0.2 Si 2.8 O 9 Cycling performance diagram of solid electrolyte matched high voltage potassium vanadium fluorophosphate positive electrode and potassium carbon composite negative electrode.

[0099] Obviously, the above specific implementations are merely examples for clear explanation, and are not intended to limit the implementations. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementations here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A novel silicon-based potassium ion solid electrolyte material, characterized in that: The chemical formula of the novel silicon-based potassium ion solid electrolyte material is K (3-x) LnP x Si (3-x) O 9, x=0~0.3, Ln is Y or Gd, each pair of silicon-oxygen tetrahedrons in the crystal framework shares a vertex, forming a silicate skeleton with [Si3O9] spiral chain as the composite group, and the anion [LnSi3O9] n 3n- The skeleton is a three-dimensional channel system, the main channels are parallel to the [100] and [010] directions, three crystallographically different K atom positions are distributed inside the skeleton, and the solid electrolyte material is a three-dimensional network structure.

2. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 1, characterized in that: The following steps are involved: Potassium salt, trivalent metal oxide, silicon dioxide and phosphate are taken as precursors, and a solvent is added at a ratio of 1 g / mL according to the mass of the precursor, and then the precursor mixture is fully ball-milled to obtain a uniform precursor mixture; the solvent is dried to remove the precursor mixture, and the mixture is placed in a muffle furnace for calcination at 500-900° C. to promote the decomposition of the precursor and the synthesis of the intermediate phase; the intermediate phase is pressurized by a unidirectional cold press at 200-400 MPa for 10-60 seconds to obtain a complete disc; the disc is calcined at 1100-1300° C. in a muffle furnace to obtain a solid electrolyte material K (3-x) LnP x Si (3-x) O9.

3. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 2, characterized in that: The potassium salt is any one of potassium carbonate, potassium acetate and potassium nitrate.

4. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 2, characterized in that: The trivalent metal oxide is any one of yttrium oxide and gadolinium oxide.

5. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 2, characterized in that: The phosphate is any one of diammonium hydrogen phosphate, monoammonium phosphate, potassium hypophosphite, and tripotassium phosphate.

6. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 2, characterized in that: The solvent is any one of isopropanol and acetone, the drying temperature is 60-120° C., and the drying time is 6-36 hours.

7. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 2, characterized in that: The calcination time at 500-900° C. is 3-12 hours.

8. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 2, characterized in that: The calcination time at 1100-1300° C. is 1-24 hours.

9. The method for preparing the novel silicon-based potassium ion solid electrolyte material according to claim 5, characterized in that: The content of the alivalent element P needs to be explored within the range of maintaining performance improvement, and its content is between 0 and 0.

3.

10. Use of any one of the novel silicon-based potassium ion solid electrolyte materials according to claims 1 to 9 as a solid electrolyte.

Citation Information

Patent Citations

  • Inorganic phosphate and uses thereof

    CN101112994A

  • Novel potassium ion solid electrolyte material and preparation method and application thereof

    CN115051026A

  • Method for improving ionic conductivity of solid electrolyte LATP

    CN115172884A

  • Eucryptite structure-based potassium ion solid electrolyte and chemical composition thereof

    CN116119678A

  • Titanate potassium ion solid fast ion conductor material and preparation method and application thereof

    CN116454366A